GROWTH COMPARISON OF MAHSEER (Tor tambroides) FROM MANNA AND TARUSAN RIVER IN WESTERN SUMATERA RIVER - Arif Wibowo; Mirna Dwirastina (Indonesian Fisheries Research Journal, 2016)
Mahseer is commonly used as a premium consumption fish with exceptional price, however, these species have encountered dwindle in distribution and abudance. The objective of this study was to investigate and to compare aspects of the interspatial variability of Western Sumatra component growth of mahseer between Manna River and Tarusan River. Mahseer samples were collected from the Manna River, Bengkulu Province and Tarusan River, West Sumatra Province. Monthly sampling was carried out over a period of February to October 2012 in Manna River and February to July 2012 in Tarusan River for detailed growth study. A total of 295 mahseer samples were collected from five sampling sites in Manna River and 495 mahseer samples were collected from three sampling sites in Tarusan River. The results show the ge group population estimation of T. Tambroides from Manna River and Tarusan River based on the analysis of length-frequencies using the Bhattacharya method, resulted in two different age groups. The theoretical growth curve for length from Manna River, the values are L¥ = 50,45 cm, K = 1,90 yr-1, t0 = -0,07 yr-1 and F  = 3,684, and for weight, the values are W¥ = 1395,49 gr, K = 0,71 yr-1, t0 = -0,078 yr-1 and F  = 6,148. The parameters of the von Bertalanffy growth curve in length from Tarusan River were L¥ = 31,34 cm, K = 1,70 yr-1, t0 = -0,09 yr-1 and F  = 3,21 and W¥ = 634,86 gr, K = 0,48 yr-1, t0 = -0,147 yr-1 and F  = 5,282 in weight.  The length-weight relationship estimated for Manna River was W = 0,000007TL3,086 for females (R2 = 0,9545, N = 91) and W = 0,0037TL1,882 for males. While for Tarusan River, length-weight relationship estimated was = 0,00003TL2,839. Mahseer from Manna River population has better growth parameters than those at Tarusan  River.